2020
DOI: 10.1016/j.bj.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of femoral head fractures

Abstract: Background Femoral head fractures (FHF) are uncommon and generally caused by high-energy injuries. Surgical reduction with stable fixation of large fragments is believed to have the best outcomes. This retrospective study intended to report outcomes with surgical treatment at our institution and tried to establish treatment algorithm. Methods Through the 6-year period (2003 – 2008) , 35 FHF in 35 consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In the systematic review by Guo et al [ 35 ], HO formation was lower in the SHD group (33.3%) compared to the S-P or K-L approaches (42.1% and 36.9%), although the difference was not statistically significant. In a study by Peng et al [ 40 ] reporting their results of treating FHFs at an average follow up of 3.3 years, 18 patients treated through the S-P approach, and 6 through the K-L approach, the overall incidence of HO was 43%. No surgical intervention was needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the systematic review by Guo et al [ 35 ], HO formation was lower in the SHD group (33.3%) compared to the S-P or K-L approaches (42.1% and 36.9%), although the difference was not statistically significant. In a study by Peng et al [ 40 ] reporting their results of treating FHFs at an average follow up of 3.3 years, 18 patients treated through the S-P approach, and 6 through the K-L approach, the overall incidence of HO was 43%. No surgical intervention was needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Del Core et al [ 29 ], 1 patient (5%) developed a postoperative infection. In a study by Peng et al [ 40 ], no deep infection was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the Pipkin type fracture is often combined with a femoral neck fracture, the possibility of postoperative femoral head necrosis is very high. It is for this reason that many studies recommend hip replacement [29,30]. At present, the surgical approach and xation methods for Pipkin type III fractures remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon should be trained and familiar with the approach, as some authors reported an inability to use this approach due to unfamiliarity. 38 …”
Section: Surgical Hip Dislocation (Shd)mentioning
confidence: 99%